Investigações dos gêneros episódio e exemplum na perspectiva sistêmico-funcional em livros didáticos de língua portuguesa do ensino fundamental - Gerhardt, Carla Carine (2017)
The purpose of this research is to investigate instantiations of anecdotes and exemplum genres in Portuguese Language textbooks used in Middle School Education, from sociocommunication purpose and the Schematic Structure of Genre (SSG) verification of these instantiations. In this study, theoretical basis of Systemic-Functional Linguistics (HALLIDAY; MATTHIESSEN, 2014) with focus on genres are used (MARTIN; ROSE, 2008; ROSE; MARTIN, 2012). The analysis focuses on genres of the story family (MARTIN; ROSE, 2008; ROSE; MARTIN, 2012), more specifically anecdote and exemplum, once the second subsidizes the teaching of values (FUZER; CASTRO; GERHARDT, 2016), and the first, a more playful teaching, especially when in the form of a joke. The sixth to ninth grade textbooks from “Português Linguagens” collections (CEREJA; MAGALHÃES, 2012) and "Projeto Teláris - Português" (BORGATO; BERTIN; MARCHEZI, 2012) were selected as the analysis universe, as they were respectively, the most distributed textbooks by PNLD in the triennium "2014 - 2016" in public Middle Schools from Santa Maria - RS, totaling eight volumes. After the stories in the textbooks were identified, potential verbal instantiations of anecdote and exemplum were collected. As a cutout, the texts in which activities proposed by the authors of the textbooks included grammatical and discursive contents were selected, constituting a corpus of 21 texts. From the linguistic analysis on the Transitivity System (HALLIDAY; MATTHIESSEN, 2014) and the Attitude subsystem from the Appraisal System (MARTIN; WHITE, 2005), it was possible to prove that, of the 21 texts, 13 instantiate the anecdote genre and 8 the exemplum genre, in addition to verify lexical-grammatical and semantic-discursive recurrences for the SSG. Material and relational clauses have been identified to introduce characters in the setting and description phases in the Orientation stage in instantiations of both genres and, specifically in the exemplum, character behaviors are represented by relational and behavioral clauses; material clauses constitute the problem in the intermediate stages and circumstances of location in time and space and negative polarities signal that problem; mental clauses perform the reaction and comment phases in the Remarkable Event stage from anecdotes, and mental, verbal and behavioral clauses constitute the reaction, comment and reflection phases in the Interpretation stage of the exemplum. Thus, what differentiates one genre from the other is the way the problem is answered: reacted in the anecdote and interpreted in the exemplum. In addition, the anecdote genre features more evaluations of Affect to fulfill its purpose, and the exemplum, judgments evaluations, for the same purpose. In activities developed by the authors of the textbooks, which contemplate the notion of genre and aspects close to the Appraisal and Ideation Systems, it was verified that the anecdote and exemplum genres were more concerned with the analysis of grammatical contents than the discursive ones in the textbooks in study.